The modification of risk assessment ranking when considering the female population and children in the INFORM risk index for selected countries - Yasir Shafiq; Ameer Muhammad; Saba Noor; Kantesh Kumar; Ume e Aimen Chhipa; Martina Valente; Junaid Razzak; Luca Ragazzoni; Francesco Barone-Adesi; Phuong Pham (Scientific Reports)
Abstract The INFORM (Index for Risk Management) identifies risk hotspots by assessing Hazard and Exposure, Vulnerability, and Coping capacity across 76 indicators. However, the original index may have overlooked the specific vulnerabilities of women and children, even within the vulnerable group in emergencies. This study recalibrated the index by redefining key indicators to better reflect risks for these groups. INFORM Index Risk formulation is “Risk = Hazard and Exposure 1/3 x Vulnerability 1/3 x Lack of coping capacity 1/3’ resulted in a total score ranging from 0 to 10, with the higher score being the higher risk. We recalibrated the 2024 INFORM Risk formula by adjusting for female and child (ages 0–14) populations in 67 countries across the Eastern Mediterranean, South Asia, and Sub-Saharan Africa. We categorized the 76 metrics as (1) those with gender-disaggregated data, (2) those adaptable for specific populations using literature, and (3) generalized indicators needing no adjustment. Shifts in risk classifications were noted among 67 countries. Initially, 13 countries (19.4%) were at ‘very high’ risk, and 18 (26.9%) were at ‘high’ risk. After recalibration, 52 countries (77.6%) showed score changes from 0.1 to 0.6 points. Six countries moved from ‘high’ to ‘very high’ risk, raising this class to 19 (28.3%). The paired t-test revealed a statistically significant difference between the original and recalibrated risk scores (mean difference = -0.17, 95% CI: -0.20, -0.13, p < 0.001). The difference in Vulnerability scores (mean difference = -0.32; 95% CI: -0.44, -0.21; p-value < 0.000) and Coping capacity (mean difference = -0.18; 95% CI: -0.23, -0.12; p-value < 0.000) were significant, derived changes in the INFORM Risk Index. The recalibrated INFORM index highlights that accurate, disaggregated data is crucial for understanding the specific needs of vulnerable populations, enabling more informed decision-making in risk management and resilience planning.